Cryptosporidium infection of stray cats in Mardin Province, Southeastern Anatolia region, Turkey - AKYILDIZ, GÜRKAN (My University, 2023)
Cryptosporidium spp. are one of the most common intestinal protozoan parasites in cats. This parasite can infect a wide range of hosts including humans and domestic animals. This aim of the study was to investigate the prevalence of Cryptosporidium spp. in stray cats of Mardin province, located in the Southeastern Anatolia region of Turkey, using microscopic and molecular methods. The result of the microscopic examination and Nested PCR, 2.5% (1/40) were positive. Sequence analysis revealed that the positive sample showed 100% similarity with Cryptosporidium felis. The result of this study indicated that Cryptosporidium spp. was detected for the first time in cats in Mardin province. Further studies are needfull to investigate in details the epidemiological status of cryptosporidiosis in domestic and stray cat populations in Mardin province of Turkey.
Keywords: Veteriner Bilimleri; Klinik Öncesi Bilimler; Veteriner Parazitoloji; Sağlık Bilimleri; Veterinary Sciences; Pre-Clinical Sciences; Veterinary Parasitology; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Bitki ve Hayvan Bilimleri; VETERİNERLİK BİLİMLERİ; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); PLANT & ANIMAL SCIENCE; VETERINARY SCIENCES; At; Veterinerlik (çeşitli); Genel Veterinerlik; Equine; Veterinary (miscellaneous); General Veterinary; Cryptosporidium felis; Microscopy and PCR diagnosis; Cat; Mardin; Turkey